2020
DOI: 10.1016/j.jpor.2019.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Precision of maxillo-mandibular registration with intraoral scanners in vitro

Abstract: Purpose: To compare the precision of maxillo-mandibular registration and resulting full arch occlusion produced by three intraoral scanners in vitro. Methods: Six dental models (groups A-F) were scanned five times with intraoral scanners (CEREC, TRIOS, PLANMECA), producing both full arch and two buccal maxillomandibular scans. Total surface area of contact points (defined as regions within 0.1 mm and all mesh penetrations) was measured, and the distances between four pairs of key points were compared, each two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 10 publications
0
62
0
5
Order By: Relevance
“…In addition, Edher et al reported that the tilting effect could occur in the area away from the section recorded by VIR in the full-arch scan [11]. In other studies, a similar effect was observed mainly in the posterior area [12,18,19]. Schmidt et al explained that the cumulative errors in superimposition and stitching processes contributed to the angular deviation in the posterior region [18].…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…In addition, Edher et al reported that the tilting effect could occur in the area away from the section recorded by VIR in the full-arch scan [11]. In other studies, a similar effect was observed mainly in the posterior area [12,18,19]. Schmidt et al explained that the cumulative errors in superimposition and stitching processes contributed to the angular deviation in the posterior region [18].…”
Section: Discussionmentioning
confidence: 92%
“…The results of this study showed that the registration of the occlusal relationship using IOSs in the edentulous area with more than two missing teeth might be clinically more inaccurate than that obtained with a laboratory scanner [12,13]. In this situation, it is recommended to apply a digital workflow including a laboratory scanner.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations